Heavy metal analysis in lens and aqueous humor of cataract patients by total reflection X-ray fluorescence spectrometry. Issue 2 (24th April 2014) - Schmeling, Martina; Gaynes, Bruce I.; Tidow-Kebritchi, Susanne
<x content-type="archive" xml:space="preserve">Abstract</x> The human eye is continuously exposed to the environment yet little is known about how much of toxins, specifically heavy metals are present in its different parts and how they influence vision and acuity. To shed light into this subject, aqueous humor and lens samples were collected from 14 cataract patients to study the presence and concentration of selected metals in the eye. Subjects undergoing routine cataract surgery were consecutively enrolled for study by simple random sampling. Prior to surgery, subject demographic were compiled. The surgical procedure involved small incision cataract removal using phacoemulsification. During the procedure, a small aliquot of aqueous humor was retained for analysis, whereas homogenized lens fragments were obtained during phacoemulsification. A balanced salt solution was used as control for each set of samples. Both ocular specimens were analyzed by total reflection X-ray fluorescence spectrometry after dilution and addition of an internal standard. The data obtained show substantial variations in elemental signature between the two media (aqueous humor and lens) and the patients themselves. Most commonly found heavy metals in both types of media were chromium and manganese. Barium was found in the lens, but not in aqueous tissue, whereas nickel was found only in the aqueous humor. Concentrations were generally higher in aqueous samples. Further study and increased sample size are required to more accurately elucidate the relationship between systemic and ocular metal accumulation and the impact of metal accumulation on measures of visual function and ocular disease.